2012
DOI: 10.4028/www.scientific.net/amr.446-449.3879
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model to Assess the Buildability of Building Structure at Design Stage in Malaysia

Abstract: Buildability is increasingly becoming a major requirement in building construction practice. The aim of buildability is to improve efficiency of the overall building process by developing construction sensitive designs. The objective of this study is to develop a model to assess the buildability of the buildings within Malaysian construction projects. To achieve the objective of this study, a structured interview with an expert panel, including 30 construction professionals, was conducted to compare the common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A research gap were identified as the existing models were mostly developed for the assessment of building projects. Previous researchers (Ugwu, Anumba, & Thorpe, 2004;Nourbakhsh et al, 2012;Lam, Wong, Chan, Shea, & Lau, 2012) had also recommended to extend their building design assessment methods to cover infrastructure projects. The researchers of the present paper intend to develop a constructability assessment models for girder bridge construction in the future.…”
Section: The Limitation Of Previous Constructability Research In Malamentioning
confidence: 99%
“…A research gap were identified as the existing models were mostly developed for the assessment of building projects. Previous researchers (Ugwu, Anumba, & Thorpe, 2004;Nourbakhsh et al, 2012;Lam, Wong, Chan, Shea, & Lau, 2012) had also recommended to extend their building design assessment methods to cover infrastructure projects. The researchers of the present paper intend to develop a constructability assessment models for girder bridge construction in the future.…”
Section: The Limitation Of Previous Constructability Research In Malamentioning
confidence: 99%
“…, 2018; Jarkas, 2010a, 2012a, b, 2016; Singhaputtangkul and Low, 2015; Lam et al. , 2007, 2012; Nourbakhsh et al. , 2012; Mydin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Buildability in construction is a project management tool for producing construction-sensitive designs (Nourbakhsh et al, 2012). Buildability promotes the optimal use of construction resources (Jadidoleslami et al, 2021;Wong et al, 2006), early integration of specialists' expert knowledge into construction designs (Mbamali et al, 2005;Nima et al, 1999), along with ease and safety of construction while meeting the client's requirements (Wong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Buildability in construction is a project management tool for producing construction-sensitive designs (Nourbakhsh et al. , 2012).…”
Section: Introductionmentioning
confidence: 99%